Pressure sensitive adhesion of an elastomeric protein complex extracted from squid ring teeth - Pena-Francesch, Abdon (2014)
The pressure sensitive adhesion characteristic of a protein complex extracted from squid ring teeth (SRT), which exhibits an unusual and reversible transition from a solid to a melt, is studied. The native SRT is an elastomeric protein complex that has standard amino acids, and it does not function as adhesives in nature. The SRT can be thermally shaped into any 3D geometry (e.g., thin films, ribbons, colloids), and it has a glass transition temperature of 32 °C in water. Underwater adhesion strength of the protein film is approximately 1.5–2.5 MPa. The thermoplastic protein film could potentially be used in an array of fields, including dental resins, bandages for wound healing, and surgical sutures in the body.